2020
DOI: 10.1109/access.2020.2995302
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum-Weighted Tensor Discriminant Analysis for Motor Imagery-Based BCI

Abstract: Spatio-temporal filtering has been widely used for extracting discriminative features in the motor imagery-based brain-computer interface (MI-BCI). In order to obtain high performance, the algorithms need to enhance robustness or find class-discriminative bands for the spatial filter. However, the existing methods either cannot derive the spatial and spectral filters with a unique objective function for guaranteeing convergence or rarely consider the combined optimization of spatial-spectral filters and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Since multiple brain regions were involved and these regions worked collaboratively in a dynamic way when the brain is processing information, the structural characteristics of the EEG signals between different dimensions (such as time, frequency, channel, etc.) would be ignored, which result in the loss of useful information in distinguishing mental workload levels [25], [26], [27]. Various studies demonstrated that the multi-dimension information of EEG signals is sensitive to the level of mental workload [6], [16], [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since multiple brain regions were involved and these regions worked collaboratively in a dynamic way when the brain is processing information, the structural characteristics of the EEG signals between different dimensions (such as time, frequency, channel, etc.) would be ignored, which result in the loss of useful information in distinguishing mental workload levels [25], [26], [27]. Various studies demonstrated that the multi-dimension information of EEG signals is sensitive to the level of mental workload [6], [16], [28].…”
Section: Introductionmentioning
confidence: 99%
“…Tensor is a representation of high-dimensional information of data, which has been widely used in the fields of gait recognition [29], image recognition [30] and so on. The intrinsic attributes of EEG data can be effectively retained by the tensorized form of representation [25], [26], [27]. In the field of brain- computer interface, Li [31] and Zhang [32] proposed EEG tensor features construction methods in decoding subjects' motion intentions in motor imagery tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, BCI faces real-world challenges, which are mostly caused by the low spatial resolution of EEG that, along with the nonstationarity present in the recorded neurophysiological signals, results in a poor signal-to-noise ratio (SNR). To enhance SNR, a regular pipeline of MI/ME processing involves the feature extraction stage using spatial filtering to increase mental states' discriminability, for which several methods are reported, like Riemannian geometry-based algorithm [12], 1 -norm unsupervised Fukunaga-Koontz transform [13], Spectrum-weighted Tensor Discriminant Analysis [14], Bayesian spatio-spectral filter optimization [15], and common spatial patterns (CSP), which maximize the variance of one class to another [16], among others. Although CSP is the most widely employed algorithm, several factors may hinder the extraction of highly separable features in terms of spatial patterns.…”
Section: Introductionmentioning
confidence: 99%